Some Thoughts On BWV 769 and 769a Canons - Anatoly P. Milka (Современные проблемы музыкознания)
J. S. Bach’s Canonic Variations are available in their original edition (BWV 769) and the autograph manuscript (BWV 769a, manuscript P 271). Remarkably, the two versions differ significantly not only in graphics and design, but also in musical composition. The comparative analysis reveals a number of oddities. The original edition, according to the title, presents the work as a cycle of variations, while the autograph version as a sequence of canons, without a hint of any variation. In this regard, of particular interest is the original printed edition. It has obvious signs it was intended for performance: a layout meant to avoid page-turning when performing the piece, an indication which hand (dextra or sinistra) to play a particular voice, signs of dynamics, the manner of performance, etc. At the same time, it has certain features that indicate the opposite. First of all, the canons in the first three variations are encrypted. Another oddity associated with the first one, yet representing a separate issue, is that the canons in the fourth and fifth variations are not encrypted. Why prompted the composer to encrypt the canons and why did he do it only in the original printed version? This is the question the article aims to answer.